FAKTOR PENENTU KEPUTUSAN PEMBELIAN KONSUMEN PADA PRODUK CHEERS KOMBUCHA - Martin, Muharies; Pahlevi, Reza Widhar (Journal Competency of Business, 2022)
This study aims to examine the effect of Brand Image, Consumer Satisfaction and Product Quality on Purchase Decision of Cheers Kombucha Products. This study uses a quantitative research approach with multiple linear regression methods. The variables used in this study were primary data which were taken directly by distributing questionnaires through the Google form and distributed to Cheers Kombucha consumers. The number of population in this study amounted to 100 people. The sample is determined by calculation using the slovin formula. The results of this study indicate that Brand Image, Consumer Satisfaction, and Product Quality have a partial effect on purchasing decisions.